Oceanography and marine environment of the Basque Country - Borja, Angel; Collins, M. B. (Elsevier oceanography series ;, 2004)
Against a background of extensive multi-disciplinary oceanographic investigations over a number of years, together with the long-term establishment of a Society and Institute, extensive information is available from studies undertaken in the estuarine and coastal waters of the Basque Country.The present authors gained access to unpublished literature and reports which, together with a synthesis of internationally-refereed papers, provide a series of scientific overviews of particular subject areas. Teams of researchers (from Basque Institutes and Universities) combine to present the present '